METODE INDUKTIF DALAM PEMURIDAN PEMUDA GEREJA DI GPdI SUMUT – ACEH - Bonnarty Steven Silalahi (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This community service activity examines the effectiveness of the inductive method in church discipleship at GPdI Sumut - Aceh, specifically among young people. The inductive method was chosen to address common hurdles among youth, such as feelings of inadequacy and a lack of theological knowledge. This method involves biblical exposition-based counseling, a presentation of the inductive method, simulation workshops, and curriculum development. The results indicate that this method successfully increases young people's participation and understanding of Bible teachings, as well as promotes the growth and multiplication of small groups. This study recommends the inductive method for Bible teaching among youth.